The role of rye bran acidification and in situ dextran formation on structure and texture of high fibre extrudates. (November 2020) - Nikinmaa, Markus; Kajala, Ilkka; Liu, Xia; Nordlund, Emilia; Sozer, Nesli
Graphical abstract: Highlights: Fermentation increased expansion of high dietary fibre bran enriched extrudates from 422 to 490%. Chemical acidification was as successful at improving properties of extrudates as fermentation. Dextransucrase treatment improved texture but not expansion of extrudates. Abstract: High insoluble dietary fibre content causes challenges with structure and texture in extrusion. This paper focused on studying the structure of extrudate enriched with rye bran modified in different ways. Fermentation of rye bran with dextran-producing Weissella confusa (with 10 g/100 g, 5 g/100 g and 0 g/100 g added sucrose as substrate for dextran production), in situ enzymatic production of dextran in the bran and chemical acidification of bran with lactic acid were compared in extrusion trials. Endosperm rye flour was the base in extrusion, of which 32 g/100 g was substituted for rye bran. Fermentation with dextran production showed similar improvement in extrudate expansion as chemically acidified bran samples (489 and 493%), in comparison with native bran (420%). Similarly, these treatments decreased extrudate hardness and increased crispiness index (CI) (16 N, 0.06 and 14 N, 0.071 respectively) compared to the control (39 N, 0.008). Enzymatically produced dextran did not affect expansion, although it decreased hardness (26 N) and increased CI compared to the control (0.023). Chemical changes in the fermented and acidified rye bran included reduction in insoluble dietary fibre (DF) (19 g/100 g → 17 g/100 g) and increase in soluble DF (5.17 g/100 g → 5.51–7.19 g/100 g), as well as soluble protein (8 g/100 g → 11 g/100 g) content. Lactic acid bacteria fermentation or acidification is therefore a promising method to increase the functionality of rye bran in extrusion.